Recovery of cefazolin and clindamycin in in vitro pediatric CPB systems. Issue 4 (6th January 2020) - Zeilmaker‐Roest, Gerdien A.; van Saet, Annewil; van Hoeven, Marloes P. J.; Koch, Birgit C. P.; van Rosmalen, Joost; Kinzig, Martina; Söergel, Fritz; Wildschut, Enno D.; Stolker, Robert J.; Tibboel, Dick; Bogers, Ad J. J. C.
Abstract: Cardiopulmonary bypass (CPB) is often necessary for congenital cardiac surgery, but CPB can alter drug pharmacokinetic parameters resulting in underdosing. Inadequate plasma levels of antibiotics could lead to postoperative infections with increased morbidity. The influence of pediatric CPB systems on cefazolin and clindamycin plasma levels is not known. We have measured plasma levels of cefazolin and clindamycin in in vitro pediatric CPB systems. We have tested three types of CPB systems. All systems were primed and spiked with clindamycin and cefazolin. Samples were taken at different time points to measure the recovery of cefazolin and clindamycin. Linear mixed model analyses were performed to assess if drug recovery was different between the type of CPB system and sampling time point. The experiments were conducted at a tertiary university hospital. 81 samples were analyzed. There was a significant difference in the recovery over time between CPB systems for cefazolin and clindamycin ( P < .001). Cefazolin recovery after 180 minutes was 106% (95% CI: 91‐123) for neonatal, 99% (95% CI: 85‐115) for infant, and 77% (95% CI: 67‐89) for pediatric systems. Clindamycin recovery after 180 minutes was 143% (95% CI: 116‐177) for neonatal, 111% (95% CI: 89‐137) for infant, and 120% (95% CI: 97‐149) for pediatric systems. Clindamycin recovery after 180 minutes compared to the theoretical concentration was 0.4% for neonatal, 1.2% for infants, and 0.6% for pediatric systems. The recovery of cefazolin was high in the neonatal and infant CPB systems and moderate in the pediatric system. We found a large discrepancy between the theoretical and measured concentrations of clindamycin in all tested CPB systems.